The information needs of health care professionals and consumers in developing countries. - Royaltey, H H (1988)
The health information needs of health care professionals and consumers in less-developed countries, although somewhat similar to those of their U.S. counterparts, have a number of unique differences. Health care professionals in developing countries are more diverse in their backgrounds, training, experience, and work settings. These differences, combined with cultural variables, a lack of resources and trained information professionals, contribute to the complexity of health information delivery. Consumers in developing countries, due to a lower literacy rate and a higher rate of commercial health information, face different problems when attempting to make health-related decisions.